The Effect of Drill Practice on Students’ Underhand Passing Skills - Aprianto, Hedro; Hermanzoni; Donie; Putra, Yogi Arnaldo (STKIP Pasundan, 2025)
This study examines the effect of drill training methods on the underhand passing skills of extracurricular volleyball students at SMAN 1 Enam Lingkung Padang Pariaman. The research used a quasi-experimental design with a one-group pretest–posttest approach. The sample consisted of eight female extracurricular players selected through purposive sampling. The research instrument used the Brumbach Forearms Pass Wall-Volley Test, and data were analyzed using the t-test. The results showed a significant improvement in underhand passing skills after the implementation of the drill method. The average pretest score was 26, while the posttest score increased to 47, with a t-count value of 51.002 greater than the t-table value of 1.860 at α = 0.05. These findings indicate that the drill method effectively enhances the accuracy and control of underhand passing among volleyball players. Thus, repetitive and systematic training is recommended to improve students’ volleyball skills.